Serum albumin levels and risk of atrial fibrillation: a Mendelian randomization study - Chen, Bohang; Wang, Chuqiao; Li, Wenjie (Frontiers in Cardiovascular Medicine, 2024)
Objective: Although several observational studies have linked serum albumin to cardiovascular disease and considered it as an important biomarker, little is known about whether increasing or maintaining serum albumin levels can effectively improve the prognosis of patients with atrial fibrillation. Therefore, this study aims to further explore the causal relationship between serum albumin and atrial fibrillation and its potential mechanism. Method: Using data from large-scale genome-wide association studies, we conducted a two-sample Mendelian randomization (MR) analysis and a mediation MR analysis, using serum albumin as the exposure variable and atrial fibrillation as the outcome variable. We included 486 serum metabolites as potential mediating factors. To increase the robustness of the analysis, we applied five statistical methods, including inverse variance weighted, weighted median, MR-Egger, simple mode, and weighted mode. Validate the MR results using Bayesian weighted Mendelian randomization method. Result: The results of the MR analysis indicate a significant inverse association between genetically predicted serum albumin concentration (g/L) and the risk of atrial fibrillation (Beta=-0.172, OR=0.842, 95%CI: 0.753-0.941, p=0.002). Further mediation MR analysis revealed that serum albumin may mediate the causal relationship with atrial fibrillation by affecting two serum metabolites, docosatrienoate and oleate/vaccenate, and the mediating effect was significant. In addition, all our instrumental variables showed no heterogeneity and level-multiplicity in the MR analysis. To verify the stability of the results, we also conducted a sensitivity analysis using the leave-one-out method, and the results further confirmed that our findings were robust and reliable.Finally, we conducted a validation using the Bayesian weighted Mendelian randomization method, which demonstrated the reliability of our causal inference results. Conclusion: This study strongly demonstrates the causal relationship between serum albumin and reduced risk of atrial fibrillation through genetic methods, and reveals the key mediating role of two serum metabolites in this relationship. These findings not only provide a new perspective for our understanding of the role of serum albumin in atrial fibrillation, but also provide new ideas for the prevention and treatment strategies of atrial fibrillation.